KINERJA Kinerja Organisasi Dan Good Corporate Governance: Pendahuluan, metode, hasil, kesimpulan - Angger Gumilang; Al Ramzy .; Wahyudin .; Zulfahri Salim; Ahmad Wahyudi Zein (CV. ITTC INDONESIA, 2025)
Performance appraisal is a systematic process carried out by organizations to assess the extent to which established goals and objectives can be achieved effectively and efficiently. Performance appraisal serves as a management evaluation tool in assessing the success of strategies, policies, and operational activities carried out. In its development, performance appraisal does not only focus on financial aspects, but also includes non-financial indicators in order to provide a more comprehensive picture of the organization's performance. The use of the Balanced Scorecard approach allows organizations to assess performance from various perspectives, namely financial, customer, internal business processes, and learning and growth. In addition, the implementation of Good Corporate Governance (GCG) plays an important role in supporting transparent and accountable performance appraisal. GCG principles can strengthen the supervisory system, increase stakeholder trust, and encourage continuous improvement in organizational performance.